Developmental outcomes for survivors of placental laser photocoagulation for the management of twin-to-twin transfusion syndrome - Angela Guzys; Susan M. Reid; Christie Bolch; Dinah S. Reddihough; Mark Teoh; Ricardo Palma-Dias; Alison Fung; Stephen Cole; Ryan Hodges; Michael Fahey; Susan P. Walker (BMC, 2023)
Abstract Background Fetoscopic laser coagulation of placental anastomoses reverses the pathological process in twin-to-twin transfusion syndrome, thereby increasing survival, but there are a paucity of studies addressing long-term neurodevelopmental outcome of survivors. This study aimed to ascertain the presence of neurodevelopmental disabilities in child survivors of monochorionic pregnancies managed by placental laser photocoagulation in the Australian state of Victoria. Methods All pregnancies undergoing placental laser photocoagulation with the Victorian Fetal Therapy Service between 2006-2017 were included. Information on each surviving child, including demographics, perinatal course, and developmental progress was collected from parents, and consent was sought to complete the Child Behaviour Checklist. Interviewers evaluated whether this information was consistent with a diagnosis of any of 14 neurodevelopmental conditions. A three-tiered outcome measure was allocated for each child: (1) unimpaired or developmentally normal, (2) mild or moderate neurological impairment, or (3) severe neurological impairment. Clinical predictors for adverse outcome were identified. Results Of 116 pregnancies (113 twin, 3 triplet), 96 (83%) resulted in 1 + surviving fetuses. 57/113 (50%) twin pregnancies resulted in 2 survivors, 36 (32%) in 1 survivor, and 20 (18%) in no survivors. Of the 235 fetuses, 154 (65.5%) survived to follow-up. Survival increased from 59% in 2006-2008 to 73% in 2015-2017. 90/154 (58%) survivors were followed up at a mean age of 7.5 [SD 3.0] years. Based on parental interview and Child Behaviour Checklist data, 28/90 (31%) participants were assessed as having neurodevelopmental impairment, 27 of mild-moderate severity and 1 severe. Speech/language disorders, attention deficit (hyperactivity) disorders, and fine motor impairment were most common. Neonatal length of stay conferred the highest risk of impairment. Conclusion Substantial variation exists between fetal therapy services in the type and length of neonatal follow-up following fetoscopic laser coagulation, contributing to a lack of data on long-term outcomes. The findings from this study support increasingly urgent calls to undertake systematic and sustained follow-up of fetoscopic laser coagulation survivors until school age. Information from this study may assist parents in their decision-making when offered fetal surgery. Importantly, it highlights a group for targeted surveillance and early intervention.